1988
DOI: 10.1017/s0890037x00032292
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy ofColletotrichum coccodesand Thidiazuron for Velvetleaf (Abutilon theophrasti) Control in Soybean (Glycine max)

Abstract: The plant pathogenic fungusColletotrichum coccodes(Cc) and the plant growth regulator thidiazuron (TDZ) were evaluated in Maryland and Quebec for velvetleaf control in ‘Williams' and ‘Maple Arrow’ soybean. TDZ was applied at 0, 0.1, 0.2, 0.3, and 0.4 kg ai/ha alone or was combined with Cc at 109spores/m2when velvetleaf was at the 1- to 2-leaf (Trial 1) or 4- to 6-leaf (Trial 2) growth stages. Velvetleaf control increased with TDZ rate, and TDZ combined with Cc further increased control. TDZ reduced velvetleaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Hughes was noticeably less effective in field trials (Wymore et al 1987;Wymore and Watson, 1989). Reduced efficacy may often be a result of lower biocontrol performance under less favourable field environments (Leger et al 2001;Netland et al 2001;Chandramohan et al 2002) and increased tolerance of plants (Hodgson et al 1988). Nevertheless, this study identified the Sencor-Ct tank mix with potential to widen the application window, as opposed to the use of the herbicide alone, for control of scentless chamomile in field.…”
Section: Discussionmentioning
confidence: 99%
“…Hughes was noticeably less effective in field trials (Wymore et al 1987;Wymore and Watson, 1989). Reduced efficacy may often be a result of lower biocontrol performance under less favourable field environments (Leger et al 2001;Netland et al 2001;Chandramohan et al 2002) and increased tolerance of plants (Hodgson et al 1988). Nevertheless, this study identified the Sencor-Ct tank mix with potential to widen the application window, as opposed to the use of the herbicide alone, for control of scentless chamomile in field.…”
Section: Discussionmentioning
confidence: 99%
“…increased pathogen infection and weed control compared with either component applied alone (Wymore et al . 1987; Hodgson et al . 1988; Wymore & Watson 1989).…”
Section: Introductionmentioning
confidence: 99%
“…and the plant growth regulator, thidiazuron (N-phenyl-NЈ-1,2,3-thiadiazol-5-yl-urea), to velvetleaf (Abutilon theophrasti Medic.) increased pathogen infection and weed control compared with either component applied alone (Wymore et al 1987;Hodgson et al 1988;Wymore & Watson 1989). Heiny (1994) found that Phoma proboscis Heiny, at 1 ¥ 10 7 spores mL -1 and applied with 2,4-D ([2,4-dichlorophenoxy]acetic acid) plus MCPP (2-[4-chloro-2-methylphenoxy]propanoic acid) at sublethal rates controlled field bindweed (Convolvulus arvensis L.) more effectively than the herbicide mixture alone and as effectively as the pathogen at a 10-fold higher rate.…”
Section: Introductionmentioning
confidence: 99%
“…Improved weed control has been reported for combined uses of fungal pathogens with synthetic herbicides (Christy et al 1993;Heiny 1994;Hodgson et al 1988;Peng and Byer 2005). Several Colletotrichum species, including C. truncatum, C. gloeosporioides (Penz) Sacc., and C. coccodes (Wallr.)…”
Section: Introductionmentioning
confidence: 99%